Prevention of White-Collar Crime by Knowledge and Learning in Business Organizations: An Empirical Study of Chief Financial Officer Management - Hans Solli-Soether; Petter Gottschalk (International School for Social and Business Studies, 2012)
Knowledge and learning are important in combating financial crime generallyand white-collar crime in particular. The purpose of this research is to generateinsights into prevention approaches in practice that may reflect on acontingent approach. The five hundred largest business companies in termsof annual turnover were identified in Norway for our empirical study of whitecollarcrime. A paper letter was mailed to the chief financial officer (CFO)asking him or her to fill in the questionnaire to be found on a web site usinga password found in the letter. The open-ended question in the questionnaireto CFOs about prevention of white-collar crime was formulated as follows:How can white-collar crime best be prevented in your company? Survey resultsindicate an even distribution of respondents emphasizing control and respondentsemphasizing influence. This empirical research steps back from manybest practice articles and provides insights into preferences of chief financialofficers on how to prevent white-collar crime in the company.